Age-stratified and blood-pressure-stratified effects of blood-pressure-lowering pharmacotherapy for the prevention of cardiovascular disease and death: an individual participant-level data meta-analysis. Issue 10305 (18th September 2021) - ,; Rahimi, Kazem; Bidel, Zeinab; Nazarzadeh, Milad; Copland, Emma; Canoy, Dexter; Wamil, Malgorzata; Majert, Jeannette; McManus, Richard; Adler, Amanda; Agodoa, Larry; Algra, Ale; et al.
Summary: Background: The effects of pharmacological blood-pressure-lowering on cardiovascular outcomes in individuals aged 70 years and older, particularly when blood pressure is not substantially increased, is uncertain. We compared the effects of blood-pressure-lowering treatment on the risk of major cardiovascular events in groups of patients stratified by age and blood pressure at baseline. Methods: We did a meta-analysis using individual participant-level data from randomised controlled trials of pharmacological blood-pressure-lowering versus placebo or other classes of blood-pressure-lowering medications, or between more versus less intensive treatment strategies, which had at least 1000 persons-years of follow-up in each treatment group. Participants with previous history of heart failure were excluded. Data were obtained from the Blood Pressure Lowering Treatment Triallists' Collaboration. We pooled the data and categorised participants into baseline age groups (<55 years, 55–64 years, 65–74 years, 75–84 years, and ≥85 years) and blood pressure categories (in 10 mm Hg increments from <120 mm Hg to ≥170 mm Hg systolic blood pressure and from <70 mm Hg to ≥110 mm Hg diastolic). We used a fixed effects one-stage approach and applied Cox proportional hazard models, stratified by trial, to analyse the data. The primary outcome was defined as either a composite of fatal or non-fatal stroke, fatal or non-fatal myocardial infarction or ischaemic heart disease, or heart failure causing death or requiring hospital admission. Findings: We included data from 358 707 participants from 51 randomised clinical trials. The age of participants at randomisation ranged from 21 years to 105 years (median 65 years [IQR 59–75]), with 42 960 (12·0%) participants younger than 55 years, 128 437 (35·8%) aged 55–64 years, 128 506 (35·8%) 65–74 years, 54 016 (15·1%) 75–84 years, and 4788 (1·3%) 85 years and older. The hazard ratios for the risk of major cardiovascular events per 5 mm Hg reduction in systolic blood pressure for each age group were 0·82 (95% CI 0·76–0·88) in individuals younger than 55 years, 0·91 (0·88–0·95) in those aged 55–64 years, 0·91 (0·88–0·95) in those aged 65–74 years, 0·91 (0·87–0·96) in those aged 75–84 years, and 0·99 (0·87–1·12) in those aged 85 years and older (adjusted pinteraction =0·050). Similar patterns of proportional risk reductions were observed for a 3 mm Hg reduction in diastolic blood pressure. Absolute risk reductions for major cardiovascular events varied by age and were larger in older groups (adjusted pinteraction =0·024). We did not find evidence for any clinically meaningful heterogeneity of relative treatment effects across different baseline blood pressure categories in any age group. Interpretation: Pharmacological blood pressure reduction is effective into old age, with no evidence that relative risk reductions for prevention of major cardiovascular events vary by systolic or diastolic blood pressure levels at randomisation, down to less than 120/70 mm Hg. Pharmacological blood pressure reduction should, therefore, be considered an important treatment option regardless of age, with the removal of age-related blood-pressure thresholds from international guidelines. Funding: British Heart Foundation, National Institute of Health Research Oxford Biomedical Research Centre, Oxford Martin School.